2016
DOI: 10.1142/s0219635216500278
|View full text |Cite
|
Sign up to set email alerts
|

A combined study of MEG and pico-Tesla TMS on children with autism disorder

Abstract: Magnetoencephalographic (MEG) recordings from the brain of 10 children with autism (6 boys and 4 girls, with ages range from 5-12 years, mean[Formula: see text][Formula: see text][Formula: see text]SD: 8.3[Formula: see text][Formula: see text][Formula: see text]2.1) were obtained using a whole-head 122-channel MEG system in a magnetically shielded room of low magnetic noise. A double-blind experimental design was used in order to look for possible effect of external pico-Tesla Transcranial Magnetic Stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Four of these papers were case-reports (Enticott et al, 2011 ; Niederhofer, 2012 ; Cristancho et al, 2014 ; Avirame et al, 2017 ), 7 were non-controlled trials (Sokhadze et al, 2010 , 2016 , 2017 ; Casanova et al, 2014 ; Wang et al, 2016 ; Abujadi et al, 2017 ; Gómez et al, 2017 ) and the remaining 12 were controlled trials (Sokhadze et al, 2009 , 2012 , 2014a , b ; Baruth et al, 2010 ; Fecteau et al, 2011 ; Casanova et al, 2012 ; Enticott et al, 2012 , 2014 ; Panerai et al, 2014 ; Anninos et al, 2016 ; Ni et al, 2017 ). Six of the controlled studies used sham rTMS as the control intervention (Fecteau et al, 2011 ; Enticott et al, 2012 , 2014 ; Panerai et al, 2014 ; Anninos et al, 2016 ; Ni et al, 2017 ) while the remaining 6 compared rTMS-treated patients with wait-list controls. Three studies recruited exclusively adult subjects to the experimental arm (Fecteau et al, 2011 ; Enticott et al, 2014 ; Ni et al, 2017 ), with the remainder focusing predominantly on children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four of these papers were case-reports (Enticott et al, 2011 ; Niederhofer, 2012 ; Cristancho et al, 2014 ; Avirame et al, 2017 ), 7 were non-controlled trials (Sokhadze et al, 2010 , 2016 , 2017 ; Casanova et al, 2014 ; Wang et al, 2016 ; Abujadi et al, 2017 ; Gómez et al, 2017 ) and the remaining 12 were controlled trials (Sokhadze et al, 2009 , 2012 , 2014a , b ; Baruth et al, 2010 ; Fecteau et al, 2011 ; Casanova et al, 2012 ; Enticott et al, 2012 , 2014 ; Panerai et al, 2014 ; Anninos et al, 2016 ; Ni et al, 2017 ). Six of the controlled studies used sham rTMS as the control intervention (Fecteau et al, 2011 ; Enticott et al, 2012 , 2014 ; Panerai et al, 2014 ; Anninos et al, 2016 ; Ni et al, 2017 ) while the remaining 6 compared rTMS-treated patients with wait-list controls. Three studies recruited exclusively adult subjects to the experimental arm (Fecteau et al, 2011 ; Enticott et al, 2014 ; Ni et al, 2017 ), with the remainder focusing predominantly on children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…One study used a pico-Tesla TMS protocol (Anninos et al, 2016 ) while two others used TBS protocols (Abujadi et al, 2017 ; Ni et al, 2017 ). Pico-Tesla TMS is a technology invented and used by a specific research group (Anninos and Tsagas, 1995 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study also revealed that miR-185 was downregulated and suppressed pancreatic cell proliferation by targeting transcriptional coactivator with PDZ-binding motif in pancreatic cancer (10). Furthermore, several miRs are reported to be promising predictors for cancer diagnosis and prognosis (11)(12)(13). Thus, investigation into the roles and functional mechanisms of miRs is crucial to NSCLC therapy.…”
Section: Introductionmentioning
confidence: 98%